Pedagogic Competency Profile: A Review of Learning Transformation as Learning Conditioning on Student Portfolio Ability - Ratnawati Susanto; Yuliati Yuliati; Yulhendri Yulhendri (Proceeding of the International Conference on Global Education and Learning, 2024)
The condition and situation of education after the Covid 19 Pandemic caused "Learning Loss" and "Learning Outcomes Loss". It takes a learning experience by providing students' reasoning insights and intellectual competence through a portfolio. The presence of educators with the ability to transform learning is needed as a learning conditioning for the ability of students' portfolios. Quantitative research using a Likert scale questionnaire instrument constructed and developed from the teacher assessment system and David M. Johnson's portfolio. The population is 80 teachers and 80 students of grade VI elementary school in the Kebon Jeruk area, West Jakarta. The findings of the study provide information that the ability of students' portfolios can be constructed and optimized through learning transformation with three dimensions in the form of active participation and success of students, assessment and feedback on the progress of learning experiences and management of students and learning materials.